COMPARATIVE STUDY OF ANTIBACTERIAL PROPERTIES OF FLAVONOIDS OF LEAVES FROM DIFFERENT CACTUS, PERENNIAL GRASSES AND MEDICINAL PLANT - Singariya, Premlata; Kumar, Mourya Krishan; Kumar, Padma (Asian Journal of Pharmaceutical Research and Development, 2018)
Comparative study of antibacterial properties of flavonoids of leaves from different Cactus (Euphorbia caducifolia); perennial grasses(Panicum antidotale and Lasiurus sindicus) and medicinal plant (Anaegissus rotundifolia) against some important bacteria (G+ve or G-ve) was done. Flavonoid extracts of leaves from all the selected plants were found to possess strong antibacterial activity against these test pathogenic microbes, as revealed by ZOI=(mm± SD), AI, MIC=(mg/ml), MMC=(mg/ml) and TA=(ml/gm) of extracts against each sensitive test pathogenic bacteria were also evaluated. Most of the pathogens were found to be sensitive against these flavonoid extracts. Free flavonoid extract of grasses and medicinal plant showed higher activity against most of the pathogens. Euphorbia caducifolia is the most inactive plant in this study. All pathogens didn’t show any activity against Euphorbia caducifolia except Proteus mirabilis which show 7.83±0.21 mm ZOI for free flavonoid. Highest ZOI (18.67±0.26) was recorded for free flavonoid of medicinal plant (Anaegissus rotundifolia) against Bacillus subtilis (G+ve bacteria) as well as other parameters like AI (1.245), MIC (0.039 mg/ml), MMC (0.78 mg/ml) were found higher against Bacillus subtilisand highest TA (1012.821 ml/gm) were found highest for free flavonoid of Lasiurus sindicus against Bacillus subtilis. The findings of the present study suggested the exploitation of flavonoid extracts of Anaegissus rotundifoliaand of Lasiurus sindicusfor future antibacterial drugs.